THE MANADO STATE UNIVERSITY LECTURER PERFORMANCE AND CAPABILITY TO ADRESS MEA - Tuegeh, Oktavia D. M. (Journal of Asean Studies on Maritime Issues, 2016)
The quality of Indonesian human resources is produced through the implementation high education quality. As an educational spearhead of high education quality creation lies in the performance of teachers and lecturers. In the Faculty of Economics, Manado State University as an object of research, there are several thing affected the lecturers performance such as the job promotion, working conditions and compensation. This study aims is to determine, to test and to analyze the effect of job promotion, working conditions and compensation on lecturer performance in Faculty of Economics, Manado State University. The sampling technique in this study is using judgment sampling method. By using multiple regressions as a data analysis tool, it is found simultaneously, job promotion, working conditions and compensation have significant effect on lecturer performance, but partially, only working conditions and compensation have significant effect while the promotion has no significant effect on the lecturers’ performance. Based on these results it is suggested to the leadership of the Faculty to continue to maintain and even improve working conditions and compensation system to lecturers to improve their performance.